The European Commission's new industrial policy - Christopher Allen; Didier Herbert; Gert-Jan Koopman (EIB Papers, 2006)
The European Commission has launched a new industrial policy for Europe, which is reviewed in this paper. While manufacturing industry remains a key building block of the European economy, it faces a number of challenges - as well as opportunities - in the form of rapid technological change; increasing trade and financial integration of the world economy; and the rise of new emerging market competitors. Whilst some sectors are performing strongly, the overall industrial structure of the EU economy makes it less than ideally positioned to face these challenges. The new industrial policy articulated by the Commission is to help the European economy adapt to the new circumstances. In contrast to old policies that sought to 'pick winners', the new approach starts from the screening of horizontal policies and framework conditions in terms of their implications for specific industrial sectors. Second, the Commission has integrated policy by bringing more closely together different policy dimensions of key relevance to various industries. Finally, the new approach attempts to achieve a greater consensus over policy, through the involvement at an early stage of key stakeholders and Member States in policy making.
Keywords: 330; Industriepolitik; EU-Staaten